Gel-Based Purification and Biochemical Study of Laccase Isozymes from Ganoderma sp. and Its Role in Enhanced Cotton Callogenesis - Kumar, Amit; Singh, Deepti; Sharma, Krishna K.; Arora, Sakshi; Singh, Amarjeet K.; Gill, Sarvajeet S.; Singhal, Barkha (Frontiers in Microbiology, 2017)
Basidiomycetous fungi, Ganoderma lucidum MDU-7 and Ganoderma sp. kk-02 secreted multiple laccase isozymes under diverse growth condition. Aromatic compounds and metal salts were also found to regulate the differential expression of laccase isozymes from both the Ganoderma sp. Laccase isozymes induced in the presence of copper from G. lucidum MDU-7 were purified by gel-based (native-PAGE) purification method. The purity of laccase isozymes was checked by zymogram and SDS-PAGE. The SDS-PAGE of purified proteins confirmed the multimeric nature of laccase isozymes. The molecular mass of isozymes was found to be in the range of 40 kDa to 66 kDa. Further, the purified laccase isozymes and their peptides were confirmed with the help of MALDI-TOF peptide fingerprinting. The biochemical characterization of laccase isozymes viz. Glac L2, Glac L3, Glac L4 and Glac L5 has shown the optimum temperature in the range of 30 ºC to 45 ºC and pH 3.0. The Km values of all the laccase isozymes determined for guaiacol were (96 µM - 281 µM), ABTS (15 µM - 83 µM) and O-tolidine (78 µM - 724 µM). Further, laccase isozymes from G. lucidum whole genome were studied using bioinformatics tools. The molecular modeling and docking of laccase isozymes with different substrates showed a significant binding affinity, which further validates our experimental results. Interestingly, copper induced laccase of 40 U/ml in culture medium was found to significantly induce cotton callogenesis. Interestingly, all the laccase isozymes were found to have an antioxidative role and therefore capable in free radicals scavenging during callogenesis. This is the first detailed study on the biochemical characterization of all the laccase isozymes purified by a gel-based novel method.